Análisis de las estrategias de comunicación política utilizadas en Tik Tok para el posicionamiento y atracción de votantes empleadas por los movimientos ADN y RC5 durante la campaña electoral de la primera vuelta 2023 - González Ordoñez, Mariángel (2024)
This thesis project focuses on conducting a study on the analysis of political communication strategies used on TikTok for the positioning and attraction of voters employed by the ADN and RC5 movements during the first round of the 2023 electoral campaign. The methodological approach was mixed, applying a description and analysis seeking to determine the relationship between two or more variables using statistical information. The sampling technique used was cluster sampling, employing hierarchical levels to assess and quantify the volume of generated posts. This project provided the opportunity to analyze how candidates leveraged this platform to communicate with voters, disseminate their proposals, create connections, and mobilize their followers. Following the application of data collection instruments, the results identified that candidates used the TikTok social network to positively position their image and thereby attract new voters. They invested in an intensive campaign through this social network to engage with people, especially the youth, and gain supporters, mobilizing followers who identified with each characteristic of the candidate. In conclusion, the election winner achieved greater interaction on TikTok, adopting a more approachable and spontaneous tone with the public. The strategies aimed to distance the candidate from the traditional stereotype, generating identity with his party through initiatives and challenges posed by the candidate on his account